Desain Pembangkit Kunci LFSR dengan Skema A5/1 Menggunakan empat Blok Bit Fungsi XOR - Teguh Septianto Nahading; Alz Danny Wowor (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
This research designs the Random Number Generator by using the LFSR with an A5/1 scheme and also four feedback for the Random Number Generator. Every feedback functions use the XOR operation to determine the new bit value in the next literation. Random results of the Run Test, Mono Bit, and Block bit shows that the algorithm is consistently able to generate random output even with various input variant. Comparison examination using previous research algorithms shows that four selected feedback functions generate random numbers. The encryption test shows that plaintext and ciphertext have “very low” and “low” correlation rates where the average correlation for every plaintext test is close to 0. The LFSR key generator with an A5/1 algorithm scheme using four XOR functions can generate very good random output for use in Stream Cipher.